Analisis bentuk Kasih Sayang Seorang Ayah kepada anaknya dalam film Miracle In Cell No.07 : Analisis isi Deskriptif - Sari, Indah Permata; Abidin, Zainal; Tayo, Yanti (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
This research examines the analysis of the form of a father's affection for his child in the film Miracle in Cell No. 07. This research uses qualitative methods to produce descriptive data in the form of written or spoken words from Film Miracle in Cell No. 07. Film is the mass media that has the most influence on imitation of human behavior patterns, sometimes information from films enters the subconscious of the human mind. This study aims to determine the form of father's affection for his child verbally and non-verbally from Film Miracle in Cell No. 07 07. Affection is a unique relationship pattern between two or more human beings. This relationship pattern is characterized by feelings of affection, mutual love, mutual love, mutual care and mutual giving, thus, it can be said that, affection is a basic human need. , so it will affect someone's life.